Is There a Principle of Targeting in Environmental Taxation? - Liu, Jianqiao; Shiell, Leslie (Université d'Ottawa | University of Ottawa, 2011)
We test whether the principle of targeting (alternatively Sandmo’s (1975) additivity property and Kopczuk’s (2003) decomposition involving the Pigovian rule) has relevance for environmental taxation in a second best world consisting of an exogenous revenue requirement and pre-existing distortionary taxes. In the context of differentiated commodity taxes, we find that Sandmo’s additivity property breaks down once one solves explicitly for the marginal cost of public funds (MCPF). Further, in the more realistic setting of a uniform commodity tax and a dedicated emissions tax, we find that the additivity property no longer holds even in the form Sandmo studied it, i.e. without solving explicitly for the MCPF. Finally, we argue that Koczuk’s decomposition is not persuasive, as it requires that a second government agency must apply a corrective tax or subsidy to adjust the choice of the Pigovian rule by the environmental agency. In a same-numbers exercise (i.e. the number of tax instruments is not increased), we show that there is no presumption in favour of a direct emissions tax over a uniform commodity tax; rather, the choice depends upon the size of the environmental damages. We conclude that there does not exist a principle of targeting in environmental taxation. / Nous considérons les implications du «principle of targeting» (soit le principe d’additivité de Sandmo (1975), soit la décomposition de Kopczuk (2003) axés sur la règle de Pigou) pour la fiscalité environnementale au deuxième rang, où le gouvernement fait face à une contrainte de revenu exogène et a recours à des taxes distortionnaires. Étant donné les taxes différenciées sur les biens, nous trouvons que le principe de l’additivité n’est pas soutenu dès qu’on solutionne pour le coût marginal du revenu public (CMRP). En plus, dans la situation plus réaliste qui consiste à une taxe uniforme sur les biens et une taxe directe sur les émissions de pollution, le principe de l’additivité n’est plus soutenu même dans le contexte prôné par Sandmo, à savoir sans solutionner pour le CMRP. Enfin, nous constatons que la décomposition de Koczuk n’est pas convaincante, car elle nécessite qu’une deuxième agence gouvernementale impose une taxe ou subvention corrective pour répond au choix d’une taxe selon la règle de Pigou par l’agence environnementale. Dans une comparaison entre une taxe uniforme sur les biens et une taxe directe sur les émissions de pollution, nous démontrons que le meilleur choix dépend du niveau des dommages. Bref, il n’y a pas de préférence systématique pour une taxe directe sur les émissions. Donc, nous concluons qu’il n’existe pas de «principle of targeting» pour la fiscalité environnementale.
Keywords: environmental taxation; second best; principle of targeting; fiscalité environnementale; politique de deuxième rang; «principle of targeting»